2018
DOI: 10.31234/osf.io/5xshq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Invisible but Unpleasant: Unconscious emotional processing of trypophobic objects

Abstract: Clusters of round objects (e.g., lotus seedpods) induce strong discomfort (trypophobic discomfort). A previous study has shown that trypophobic discomfort stems not only from middle but also low spatial frequency information, which should be rapidly transmitted to the amygdala via the superior colliculus and pulvinar pathway. Based on this finding, we hypothesized that trypophobic discomfort would be evoked by invisible trypophobic images; the present study examined this using a backward masking technique. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…29,30 However, other phantoms and in vivo studies have demonstrated a significant ADC difference among different magnet fields. 31,32 Therefore, Sasaki et al 31 have suggested using rADC values because they might be more suitable than absolute ADC values for evaluating diffusion abnormalities acquired in different scanners and field strengths. ROIs drawn on the normal-appearing white matter 33 or gray matter 11 are commonly used for ADC normalization.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 However, other phantoms and in vivo studies have demonstrated a significant ADC difference among different magnet fields. 31,32 Therefore, Sasaki et al 31 have suggested using rADC values because they might be more suitable than absolute ADC values for evaluating diffusion abnormalities acquired in different scanners and field strengths. ROIs drawn on the normal-appearing white matter 33 or gray matter 11 are commonly used for ADC normalization.…”
Section: Discussionmentioning
confidence: 99%
“…The more meaningful stimuli are, as in Jioang et al, the more likely they capture attention even under subliminal conditions. Tsikandilakis et al (2021) Aligning with past evidence on individuals reacting to invisible negative emotionrelated or emotion-inducing cues (Sagliano, Maiese, & Trojano, 2020;Sasaki, Watanabe, Yamada, 2018;Vizueta, et al, 2012;Zald, 2003), Jiang's study introduced sex-related stimuli to spatial attention and found strong results. The unconscious side of sexual preferences is a rarely explored aspect of cognitive psychology.…”
Section: Introductionmentioning
confidence: 60%
“…Another study revealed that low-and mid-spatial frequency information contributed to trypophobia (Sasaki et al, 2017). Based on these findings, trypophobic objects may be processed rapidly and unconsciously; indeed, there is empirical evidence supporting this (Sasaki, Watanabe & Yamada, 2018;Shirai & Ogawa, 2019). Taken together, early visual processing plays key roles in trypophobia.…”
Section: Introductionmentioning
confidence: 94%